Comprehensive evaluation of therapeutic effectiveness and safety profiles of baloxavir marboxil for managing influenza virus infection in pediatric populations: a systematic review with pooled meta-analytic data - Ji, Yishu; Yang, Wenwen; Wang, Weijie (Frontiers in Pediatrics, 2026)
ObjectiveThis systematic review aimed to assess the clinical effectiveness and safety profile of baloxavir marboxil for managing influenza in pediatric populations.MethodsThis review has been registered on the INPLASY platform (INPLASY2025110063). Designed in accordance with the PRISMA 2020 guidelines, we searched four major biomedical databases (PubMed, Embase, Web of Science, Cochrane Library) covering publications from January 1, 2015, to January 30, 2025. Eligibility criteria encompassed both randomized controlled trials and observational cohort studies evaluating this antiviral agent in children with laboratory-confirmed influenza. Methodological rigor was appraised using the Cochrane Collaboration's risk of bias instrument for randomized controlled trials (RCTs) and the Newcastle-Ottawa Quality Assessment Scale for cohort studies. Statistical synthesis was conducted using RevMan 5.3 software (Version 5.3.5) with metafor package implementation.ResultsOur analysis incorporated 12 clinical investigations involving a total of 4,586 patients. A random-effects model meta-analysis demonstrated that, compared to neuraminidase inhibitors (oseltamivir, zanamivir, peramivir, laninamivir), baloxavir marboxil achieved accelerated resolution of febrile symptoms (MD = −13.16 h, 95% CI: −19.16 to −7.15, P < 0.0001). Subgroup analyses stratified by viral subtype demonstrated consistent therapeutic advantages in influenza A infections (random-effects model, MD = −9.40 h, 95% CI: −18.31 to −0.49, P = 0.04), particularly regarding time to symptom alleviation (fixed-effect model, MD = −8.50 hours, 95% CI: −13.14 to −3.86, P = 0.0003). Safety assessments indicated a 59% reduction in drug-related adverse events relative to oseltamivir (fixed-effect model, OR 0.41, 95% CI 0.31–0.56; P < 0.001), while total adverse event rates showed comparable incidence between treatment arms (fixed-effect model, OR = 0.85, 95% CI: 0.69–1.05, P = 0.14).ConclusionThese findings suggest baloxavir marboxil demonstrates faster fever resolution and a favorable safety profile in pediatric influenza management. However, continuous monitoring for baloxavir-resistant mutations (such as PA/I38T) in the pediatric population is warranted. Furthermore, confirmation through large-scale multicenter trials with extended follow-up periods remains warranted.